Prevalence and Predictors of Postpartum Depression among Mothers Attending Tertiary Care Hospital, Jammu, India - Bala, Jyoti; Kumari, Rashmi; Gupta, Rajiv Kumar; Langer, Bhavna; Mahajan, Richa; Zaffer, Imran (National Journal of Community Medicine, 2024)
Background: Postpartum depression refers to non-psychotic depressive episode that begins immediately after childbirth. Although delivering a baby is a happy event but many females develop depressive symptoms. About 13% of postpartum women experience a mental disorder, primarily depression worldwide. The aim is to estimate the prevalence of Postpartum depression among the mothers and to determine the association of Perceived Social Support, socio demographic and other obstetric variables with Postpartum depression. Methodology: The study was conducted among the Postpartum mothers attending the immunization section of a Tertiary care hospital, Jammu, India. Tools used are- Edinburgh Postnatal Depression Scale (EPDS), Hamilton depression Rating Scale (HDRS) and Multidimensional Scale of Perceived Social Support (MSPSS). SPSS software was used to analyse the data. Results: Prevalence of Postpartum Depression was found to be 16.1%. Variables like residence, occupation, h/o domestic violence, family h/o mental illness, eventful antenatal period, h/o hospitalization of baby, unwanted parenthood and low social support emerged to be independent predictors of Post Partum depression. Conclusions: Postpartum mothers particularly those, who were having poor social support are highly vulnerable to depression. Every postpartum mother should be screened for postpartum depression and timely referred to the psychiatrists. Also, family members need to be counselled.